A IMPORTÂNCIA DA INDÚSTRIA DE TERCEIRIZAÇÃO DE FROTA PARA GERAÇÃO DE VALOR EM NEGÓCIOS - Romão, Fernando César (2008)
It presents a financial model to evaluate Fleet Outsourcing Industry for Organizations with operations in all regions in Brazil. It includes a sector description, with historical vision and economic importance in Brazilian scenario , and services offered through presentation. The Results show us significant advantages to Fleet Outsoursing taking into account the work assumptions to be considered.